Bioengineering Techniques for Soil Erosion Protection and Slope Stabilization - Julia Georgi; Ioannis Stathakopoulos (European Regional Science Association (ERSA), 2006)
The use of bio-engineering methods for soil erosion protection and slope stabilization has a long tradition. Old methods with rocks and plants, structures of timber have been used over the past centuries. Recently these old soil conservation and stabilization techniques have been rediscovered and improved. Biotechnical engineering methods have become part of geotechnical and hydraulic engineering and have helped bridge the gap between classical engineering disciplines, land use management, landscape architecture and biological sciences. In this paper the different uses of plants in hydraulic and geotechnical engineering design are presented. The core of this study is a comprehensive overview of the most important biotechnical construction methods used for soil erosion protection and slope stabilization. Methods, construction procedure, and the major advantages and disadvantages of these biotechnical methods are discussed. Considerations about construction and maintenance costs conclude in this paper.
Keywords: 330